Patients attitudes towards sleep disturbances during chemotherapy. (16th August 2013) - Romito, F.; Cormio, C.; De Padova, S.; Lorusso, V.; Berio, M.A.; Fimiani, F.; Piattelli, A.; Palazzo, S.; Abram, G.; Dudine, L.; Guglielmi, A.; Galise, I.; et al.
<x xml:space="preserve">Abstract</x> Sleep disturbances are among the most distressing symptoms in cancer: they often co‐occur with fatigue, pain and psychological distress. Despite the negative impact on quality of life, patients rarely seek help for managing their sleep disturbances. This paper presents the results of a multicentre observational study on patients' attitudes towards their sleep problems. The study also investigates symptom correlates. Patients responded to a semi‐structured interview and completed the following questionnaires: Pittsburgh Sleep Quality Index; Brief Fatigue Inventory; Hospital Anxiety and Depression Scale; and European Organisation for Research and Treatment of Cancer (EORTC) Quality of Life QLQ‐C30 Questionnaire (QLQ‐C30). Four hundred and three cancer patients were enrolled in the study. Bad sleepers constituted 66% of the sample. Thirty‐eight per cent of them had not turned to any professional to solve their sleep disturbances because they had various beliefs about the importance of the problem and the possibility to be treated. The main correlates of sleep disturbances were psychological distress, reduced physical functioning and reduced overall quality of life. In conclusion, there is a need to sensitise patients to actively search for a solution to their sleep disturbances so they can be solved along with other co‐occurring symptoms. Doctors could also be encouraged to dedicate more attention to routinely asking cancer patients about eventual sleep disturbances.